Mucinous cystic neoplasm of the liver with extrahepatic growth presenting with ascending cholangitis diagnosed by endoscopic ultrasound features: a case report - Tanawat Pattarapuntakul; Bancha Ovartlarnporn; Jaksin Sottisuporn (Journal of Medical Case Reports, 2018)
Abstract Background Mucinous cystic neoplasm of the liver with extrahepatic growth is a rare benign epithelial neoplasm of the biliary system that presents with a mass effect or is incidentally found on imaging. The tumor affects mostly the common hepatic duct, which is difficult to diagnose preoperatively by radiology, endoscopy, or cystic fluid analysis. Endoscopic ultrasound is a noninvasive tool for the evaluation of features of a cystic lesion and the extent of disease. Optimal treatment is complete tumor resection. Case presentation A 27-year-old Thai woman was referred to our hospital for investigation and treatment of clinical symptoms of obstructive jaundice and ascending cholangitis, as well as an unknown cause of obstruction. Multiple investigations were performed, including endoscopic retrograde cholangiography and magnetic resonance imaging. Endoscopic ultrasound showed a multiloculated cystic lesion with internal septations without communication to the bile duct, which helped to support a diagnosis of mucinous cystic neoplasm. Eventually, the pathological diagnosis made was mucinous cystic neoplasm of the bile duct. A follow-up clinical examination with imaging at 6 months revealed that the patient was asymptomatic and without recurrence. Conclusions We report a rare case of a patient with a large mucinous cystic neoplasm of the liver with extrahepatic growth causing biliary obstruction, which was diagnosed on the basis of endoscopic ultrasound features. Following definitive diagnosis, treatment with complete surgical resection using a multidisciplinary approach was successful.